Reproductive biology of NW Mediterranean tonguefish Symphurus nigrescens and Symphurus ligulatus. (20th February 2015) - Bustos-Salvador, F.; Fernandez-Arcaya, U.; Ramirez-Llodra, E.; Aguzzi, J.; Recasens, L.; Rotllant, G.; Company, J.B.
Abstract : The population structure and reproductive biology of deep-water continental margin Cynoglossidae is poorly known. Here, we focused on two highly abundant species of the upper slope of the NW Mediterranean Sea, Symphurus nigrescens and S. ligulatus. Megafaunal sampling of 37 hauls was conducted between April 2003 and May 2004 in the Blanes canyon and the adjacent open slope between 300–1500 m depth. The differential bathymetric distribution between the two species was surveyed by standardizing catch data per unit of swept surface and by pooling resulting densities by 100 m depth interval. Females of both species were classified into a five-stage maturity scale according to their external appearance and their gonads dissected for histological analysis. The analysis of the species' bathymetric distribution revealed a differential and only partial overlap. In both species, an increase in size with depth was observed coinciding with the dominance of females in deeper depth strata. The shallower species, S. nigrescens showed a marked spawning period with a peak in summer. In contrast, the deeper-living species, S. ligulatus, presented a longer spawning period ranging from spring to autumn. Moreover, histological examination demonstrated that the ovaries of both species had an asynchronous organization. Present results on spatial-temporal size frequency distribution, spawning temporality and oocyte size are discussed assuming interspecific competition and the different environmental conditions related to their bathymetric distribution.